The Role of Green Human Resources and Supply Chain Management on the Sustainability Performance (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to analyze the effect of human resource management and green supply chain management on the company’s sustainability performance. This research uses quantitative methods. This research was tested using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Research data use medium and large category manufacturing (manufacturing) companies in KEPRI Province in 2021. The results show that green human resource management has a positive and significant effect on sustainability performance while supply chain management does not affect sustainability performance. In the next study, it is recommended to use mixed methods through questionnaires and interviews so that the data obtained is more complete.